A Mixed-Methods Process Evaluation of the Art of Yoga Project for Girls in Custody - Middleton, Lisa (The prison journal, 2019)
Many adolescent girls in custody have extensive histories of profound childhood trauma and abuse. They typically come from marginalized communities marked with gang violence. The Art of Yoga Project provides a gender-specific, trauma-informed, and culturally sensitive approach to cater to this understudied and underserved population. The Yoga and Creative Arts Curriculum combines yoga, mindfulness, meditation, and art for girls in custody in several Californian counties. The findings are from a mixed methods evaluation of multiple sites over several years. Taken together, we saw an improvement in the self-reported emotional regulation of incarcerated girls. We discuss practical implications for extending this work in other jurisdictions and to other populations.